Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 39



Work Step by Step

$(fg)(x)=f(x)g(x)$ $(fg)(-2)=f(-2)g(-2)$. First, find $f(-2)$ and $g(-2)$. $f(-2)=(-2)^{2}+4\times(-2)=4-8=-4$ $g(-2)=2-(-2)=2+2=4$ Then, multiply them. $(fg)(-2)=f(-2)g(-2)=-4\times4=-16$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.